Variations in physical, chemical and biological properties in relation to sludge dewaterability under Fe (II) – Oxone conditioning - Xiao, Keke (2017)
The mechanism of Fe (II) – oxone conditioning to improve sludge dewaterability was investigated in this study. Five different types of sludge were tested, including raw sludge (Group 1: mixed primary and secondary sludge, waste activated sludge and anaerobic digested sludge) and pretreated sludge with prior solubilisation (Group 2: ultrasonic or thermal pretreated sludge). After Fe (II) – oxone conditioning, the concentrations of dissolved organic carbon, protein and polysaccharide of soluble extracellular polymeric substances (SB EPS) increased for Group 1, but decreased for Group 2. For all types of sludge investigated, the related organic compounds of loosely bound (LB) and tightly bound (TB) EPS decreased with Fe (II) – oxone conditioning, and increased sludge filterability showed strong and positive correlation with the removal of low molecular weight protein and neutrals in LB EPS. Fe (II) - oxone was very effective in disintegrating cell membrane and caused potential cell lysis, as indicated by increased percentage of damaged microbial cells. From this study, the mechanism of Fe (II) - oxone conditioning was proposed and can be divided into two steps: (1) Oxidation step – sulfate radicals degraded organic compounds in LB and TB EPS in sludge and transformed bound water to free water that was trapped in TB and LB EPS; It also damaged cells membrane and may help to release intracellular water content. Sludge flocs were broken into smaller particles; (2) Coagulation step - Fe (III), generated from the oxidation step can act as a coagulant to agglomerate smaller particles into larger ones and reduce the repulsive electrostatic interactions. Combined effects from above two steps can greatly improve sludge filterability.